Iowa RBA, August 17, 1998 - Fuller, James L.et al; Iowa Ornithologists' Unionet al (1998)
Email for the Iowa RBA for August 17, 1998. Highlights include Red-necked Phalarope, Snowy Egret, and Piping Plover. Includes notes for updates for August 18, and August 19. Epson - sheet feed/flatbed